A case study of katabatic winds over Schirmacher Oasis, east Antarctica (MAUSAM, 2003)
Katabatic winds are a regular feature during night and early morning hours over valleys and low lying areas adjacent to high terrains. In Antarctica, the mass of the earth in the form of plateau is covered with full of ice and has a downslope from the South Pole everyside upto the coast. Due to cooling of air near the ground as well as due to pressure  gradient, the coastal belt often experiences strong winds blowing down the slope of the plateau. In this study “katabatic wind” at Maitri over Schirmacher Oasis has been examined using the data collected during the 9th Indian Antarctic Expedition 1990-91. The primary results show that katabatic winds are observed in all the months with higher frequency and strength in winter compared to other seasons. A distinction between pure katabatic wind and extraordinary katabatic wind is done based on the wind direction and associated changes in the surface temperature and weather conditions.